Differential interaction with TREM2 modulates microglial uptake of modified Aβ species. Issue 12 (24th August 2021) - Joshi, Pranav; Riffel, Florian; Satoh, Kanayo; Enomoto, Masahiro; Qamar, Seema; Scheiblich, Hannah; Villacampa, Nàdia; Kumar, Sathish; Theil, Sandra; Parhizkar, Samira; Haass, Christian; Heneka, Michael T.; et al.
Abstract: Rare coding variants of the microglial triggering receptor expressed on myeloid cells 2 (TREM2) confer an increased risk for Alzheimer's disease (AD) characterized by the progressive accumulation of aggregated forms of amyloid β peptides (Aβ). Aβ peptides are generated by proteolytic processing of the amyloid precursor protein (APP). Heterogeneity in proteolytic cleavages and additional post‐translational modifications result in the production of several distinct Aβ variants that could differ in their aggregation behavior and toxic properties. Here, we sought to assess whether post‐translational modifications of Aβ affect the interaction with TREM2. Biophysical and biochemical methods revealed that TREM2 preferentially interacts with oligomeric Aβ, and that phosphorylation of Aβ increases this interaction. Phosphorylation of Aβ also affected the TREM2 dependent interaction and phagocytosis by primary microglia and in APP transgenic mouse models. Thus, TREM2 function is important for sensing phosphorylated Aβ variants in distinct aggregation states and reduces the accumulation and deposition of these toxic Aβ species in preclinical models of Alzheimer's disease. Main Points: TREM2 differentially recognizes distinct post‐translationally modified Aβ variants Phosphorylation of Aβ increases binding to TREM2 TREM2 modulates differential uptake of Aβ variants by microglia and their deposition in the brain